2021
DOI: 10.1002/ldr.4112
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem restoration through aerial seeding: Interacting plant–soil microbiome effects on soil multifunctionality

Abstract: Understanding the driving factors of soil multifunctionality is of great significance for the protection and restoration of degraded terrestrial ecosystems. However, the effects of above‐ and belowground factors are rarely evaluated simultaneously, and the driving mode of both factors on soil multifunctionality is not clear. Here, we evaluated the restoration of mobile dunes threatened by desertification through aerial seeding, that is, the sowing of seeds through aerial devices, from 1983 to 2015 in Mu Us Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
1
14
0
1
Order By: Relevance
“…Fungi often play a crucial role in the initial stages of colonization and can significantly influence plant community establishment (Eichorst et al, 2011; Pankratov et al, 2011). As the restoration process extends, the overall population of soil bacteria may become the dominant driving force for soil multifunctionality (Liu et al, 2021), consistent with this study. Studies should consider exploring the relationship between microbial diversity and soil multifunctionality during different restoration stages.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fungi often play a crucial role in the initial stages of colonization and can significantly influence plant community establishment (Eichorst et al, 2011; Pankratov et al, 2011). As the restoration process extends, the overall population of soil bacteria may become the dominant driving force for soil multifunctionality (Liu et al, 2021), consistent with this study. Studies should consider exploring the relationship between microbial diversity and soil multifunctionality during different restoration stages.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with many previous studies on the changes of microbial diversity and soil physicochemical and soil enzyme activities in mining areas (Guan et al, 2020; Li et al, 2019; Lozano et al, 2014; Wang et al, 2013). Soil TC and soil TN, and soil enzyme activities involved in the carbon and nitrogen cycle have been significantly increased, which had accumulated favorable soil nutrient and provided more stable resources for the growth of soil microorganisms (Liu et al, 2021). This result demonstrated that reforestation had positive effects on soil quality and soil microbial diversity perspective for a certain period of reclamation (Jurburg & Salles, 2015; Philippot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of soil EMF was aided by vegetation regeneration (Figure 3). Indicating that higher soil nutrient content and availability encouraged soil microbial proliferation, accelerated the geochemical cycling of soil nutrients, and ultimately improved soil ecological functions, soil EMF was significantly associated with soil nutrients, microbial biomass, and EEA (Figure 4A, Figure S1) (Fry et al, 2018;Liu et al, 2021;Ma et al, 2022). Soil nutrients greatly influenced how soil enzyme response to vegetation restoration (Figure 4A; Guo et al, 2022).…”
Section: Effect Of Vegetation Restoration On Soil Ecosystem Multifunc...mentioning
confidence: 99%
“…The first analyses of the water and soil of the still shrinking Aral Sea revealed microbial communities related to hypersaline-adapted bacteria and archaea; most of the archaeal sequences were phylogenetically affiliated with the order Halobacteriales but also indicated the presence of novel lineages ( 3 , 8 ). Recent findings showed the importance of the members of the local plant-associated microbiota, especially those inhabiting the below-ground compartments, for ecosystem functioning during natural restoration ( 9 , 10 ). Microbes can accelerate the decomposition of litter and the circulation of soil nutrients; both processes are important for soil multifunctionality during restoration.…”
Section: Introductionmentioning
confidence: 99%